1998
DOI: 10.1046/j.1365-8711.1998.01395.x
|View full text |Cite
|
Sign up to set email alerts
|

Meteor observations in Japan: new implications for a Taurid meteoroid swarm

Abstract: Observational evidence is sought that the long‐term (104 yr) action of a mean motion resonance with Jupiter can produce structure in a meteoroid stream, concentrating meteoroids in a dense swarm. More specifically, predictions tabulated by Asher & Clube of enhanced meteor and fireball activity from a Taurid Complex swarm in the 7:2 resonance are compared with observational data collected in Japan over several decades. The swarm model was proposed for reasons independent of the observations analysed here, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 10 publications
(11 reference statements)
1
43
0
Order By: Relevance
“…Since the Earth does not encounter the new branch every year, it is evident that meteoroids of the new branch are not spread along the whole orbit. The model and observations of and Asher & Izumi (1998) suggest that the enhanced activity of Taurids is caused by a resonant swarm of meteoroids, which extends ±30-40…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Since the Earth does not encounter the new branch every year, it is evident that meteoroids of the new branch are not spread along the whole orbit. The model and observations of and Asher & Izumi (1998) suggest that the enhanced activity of Taurids is caused by a resonant swarm of meteoroids, which extends ±30-40…”
Section: Discussionmentioning
confidence: 85%
“…Asher & Izumi (1998) showed that enhanced Taurid activity indeed occurred in the years when the center of the swarm was less than 40…”
Section: Introductionmentioning
confidence: 99%
“…In fact, larger particles are preferentially concentrated in the vicinity of comet orbits (Asher and Izumi, 1998;Dubietis and Arlt, 2007), as observed directly in dust trails (Sykes et al, 1986). Finally, larger masses tend to generate significant amounts of micrometre-sized "smoke" particles upon infall ( Klekociuk et al, 2005) that may be particularly conducive to generation of methane via UV photolysis due to their large amount of freshly-exposed surface area.…”
Section: The Methane Sourcementioning
confidence: 94%
“…One reason this assumption may not hold even for a dense stream is if grains are azimuthally confined along the orbit by mean motion resonances [ Asher et al , ]. For the Encke meteor stream, there is evidence that large ( centimeter‐sized) grains within the 7:2 mean motion resonance with Jupiter lead to episodic outbursts of bright Taurid meteors at the Earth [ Asher and Clube , ; Asher and Izumi , ]. The annual repeatability of the feature seen in Mercury's exosphere [ Burger et al , ] suggests that if due to impact vaporization, such a population of resonant grains is not the culprit.…”
Section: Simulation Setupmentioning
confidence: 99%